Factor Analysis on Product Quality that Contributes and Affects Customer Satisfaction (Case Study on Muslim Women's Fashion Clothing Brand in Malang Raya) - Riesta Devi Kumalasari (Tourism Department, State Polytechnic of Banyuwangi, 2024)
The purpose of this study is to determine the quality of Muslim Women's fashion products in Malang Raya when measured by the attributes of performance, specialty, reliability, conformity with specifications, durability, serviceability, and perceived quality; determine customer satisfaction of Muslim Women's clothing fashion product when measured by attributes of product quality, service quality, ease of getting products, prices, and how to advertise products, and determine the influence between product quality and customer satisfaction of Muslim Women's clothing fashion product in Malang Raya. The method used in this study was a quantitative descriptive method with data obtained through questionnaires with respondents of 78 Muslim female customers. The data analysis technique used in this study is multiple linear regression using the SPSS application. The result of this study is 7 attributes in the product quality variable including performance, privilege, reliability, suitability, durability, service ability and quality perceived by some respondents in this study have a high level and 5 attributes in the customer satisfaction variable include product quality, service quality, ease of getting products, prices, and how to advertise products most respondents in this study have a high level keep. Thus, it can be concluded that the research hypothesis that states there is a significant influence on the quality variables of Muslim Women's fashion products and variables related to customer satisfaction can be accepted and tested.